Persepsi Emak-Emak Terhadap Film Layangan Putus Studi Deskriptif Warga Kampung Ledok Kec. Kaliwates Kab. Jember - Ferdian Ardani Putra; Syafri Affandhi (Medio Jurnal Ilmu Komunikasi, 2023)
Film is not only a medium of entertainment, but also has an element of learning in it, including the film "Layangan Putus" which tells about the realities of household life so that this film is in great demand among housewives. This research was conducted in Ledok Village, Jember Lor District, Kec. Kaliwates. The focus of the research is "How are the perceptions of the mothers of Ledok Village Rt. 3 RW. 6, Kelurahan Jember Kidul for the film “Layangan Putus”. This research uses a descriptive qualitative research type, data collection techniques including; observation, interview, and documentation. Analysis of the data researchers used the Miles Huberman model which included data reduction, data presentation, drawing conclusions and the validity of the data used was technique and source triangulation. The results of the study showed that mothers' interest in the film Layangan Putus was because the storyline presented by the film was quite good and viral on social media. The mothers also admitted that they were carried away emotionally while watching the film. Mothers also perceive from the film that they are honest and open to each other in the household so that the relationship does not end in separation